Factors affecting willingness to receive a kidney transplant among minority patients at an urban safety-net hospital: a cross-sectional survey. Issue 1 (December 2015) - Ilori, Titilayo; Enofe, Nosayaba; Oommen, Anju; Odewole, Oluwaseun; Ojo, Akinlolu; Plantinga, Laura; Pastan, Stephen; Echouffo-Tcheugui, Justin; McClellan, William
Abstract Background In the US, African Americans (AAs) are four times more likely to develop end stage renal disease (ESRD) but half as likely to receive a kidney transplant as whites. Patient interest in kidney transplantation is a fundamental step in the kidney transplant referral process. Our aim was to determine the factors associated with the willingness to receive a kidney transplant among chronic kidney disease (CKD) patients in a predominantly minority population. Methods CKD patients from an outpatient nephrology clinic at a safety-net hospital (n = 213) participated in a cross-sectional survey from April to June, 2013 to examine the factors associated with willingness to receive a kidney transplant among a predominantly minority population. The study questionnaire was developed from previously published literature. Multivariable logistic regression analysis was used to determine factors associated with willingness to undergo a kidney transplant. Results Respondents were primarily AAs (91.0 %), mostly female (57.6 %) and middle aged (51.6 %). Overall, 53.9 % of participants were willing to undergo a kidney transplant. Willingness to undergo a kidney transplant was associated with a positive perception towards living kidney donation (OR 7.31, 95 % CI: 1.31–40.88), willingness to attend a class about kidney transplant (OR = 7.15, CI: 1.76–29.05), perception that a kidney transplant will improve quality of life compared to dialysis (OR = 5.40, 95 % CI: 1.97–14.81), and obtaining information on kidney transplant from other sources vs. participant's physician (OR =3.30, 95 % CI: 1.13–9.67), when compared with their reference groups. Conclusion It is essential that the quality of life benefits of kidney transplantation be known to individuals with CKD to increase their willingness to undergo kidney transplantation. Availability of multiple sources of information and classes on kidney transplantation may also contribute to willingness to undergo kidney transplantation, especially among AAs.